Der Mietvertrag mit mehreren Mietern Unter besonderer Berücksichtigung der Wohn- und Geschäftsraummiete - Ackermann, Ruedi (sui generis Verlag, 2023)
Tenancy agreements with several tenants are widespread (e.g. shared apartments or rent by married or unmarried couples). A joint tenancy also arises in the case of inheritance, if the deceased tenant leaves several heirs. Joint tenancy of business premises is also one of the typical forms of tenancy. Tenancy law does not contain any special regulations on joint tenancy. The legal questions that arise are to be answered according to the general legal norms of private law. The present work offers a systematic presentation of the tenancy agreement with several tenants and deals mainly with the origin of the joint tenancy, the internal relationship between several tenants and the termination of the tenancy agreement. Translated with www.DeepL.com/Translator (free version)